Identification and characterization of abundant repetitive sequences in Eragrostis tef cv. Enatite genome. Issue 1 (December 2016) - Gebre, Yohannes; Bertolini, Edoardo; Pè, Mario; Zuccolo, Andrea
Abstract Background Eragrostis tef is an allotetraploid (2n = 4 × = 40) annual, C4 grass with an estimated nuclear genome size of 730 Mbp. It is widely grown in Ethiopia, where it provides basic nutrition for more than half of the population. Although a draft assembly of theE. tef genome was made available in 2014, characterization of the repetitive portion of theE. tef genome has not been a subject of a detailed analysis. Repetitive sequences constitute most of the DNA in eukaryotic genomes. Transposable elements are usually the most abundant repetitive component in plant genomes. They contribute to genome size variation, cause mutations, can result in chromosomal rearrangements, and influence gene regulation. An extensive and in depth characterization of the repetitive component is essential in understanding the evolution and function of the genome. Results Using new paired-end sequence data and a de novo repeat identification strategy, we identified the most repetitive elements in theE. tef genome. Putative repeat sequences were annotated based on similarity to known repeat groups in other grasses. Altogether we identified 1, 389 medium/highly repetitive sequences that collectively represent about 27 % of the teff genome. Phylogenetic analyses of the most important classes of TEs were carried out in a comparative framework including paralog elements from rice and maize. Finally, an abundant tandem repeat accounting for more than 4 % of the whole genome was identified and partially characterized. Conclusions Analyzing a large sample of randomly sheared reads we obtained a library of the repetitive sequences ofE. tef . The approach we used was designed to avoid underestimation of repeat contribution; such underestimation is characteristic of whole genome assembly projects. The data collected represent a valuable resource for further analysis of the genome of this important orphan crop.